The Variety trail results of food and fodder barleys in central agricultural zone - Zorigt, Erdenechimeg; Nyamdavaa, Tsolmon; Azjargal, Sarantsetseg; Byambaa, Odgerel (Mongolian Journal of Agricultural Sciences, 2020)
The new varieties of barley, which is adapted to the drought conditions of our country, are indispensable. The main task of this study focused on the identification of barley varieties in the soil and climatic conditions of the central region of cultivation and the identification of high-yielding, disease-resistant, drought-resistant, and grade-resistant barley varieties. There were tested a total of 14 varieties of barley for food, forage and beer, are compared with standard variety by yield and other quality indicators, the maturation periods were ranged 88-106 days for experimental varieties, while there were yielded 2.2-14.7 c / ha, 6.0-14.8 c / ha and 2.0-4.5 c / ha for the beer, forage and food varieties, respectively. The beer variety MonPiBarley-5 and line PA-459 yielded 4.3-5.4 c / ha more than the standard varieties, but the line TA-453 had grown 8.8 cm higher than standard feed variety. However, the data presented here tested varieties no exceed the yield of the standard variety. Газар тариалангийн төв бүсэд хүнс, тэжээлийн зориулалттай арвайн сортуудыг сорьсон дүн Манай орны гандуу хуурай цаг уурын нөхцөлд зохицсон арвайн шинэ сортыг сорьж туршин, үйлдвэрлэлд нэвтрүүлэх шаардлага хэрэгцээ нилээд гарч байна. Энэ судалгаа нь тариалангийн төв бүсийн хөрс, цаг уурын нөхцөлд дасан зохицож ургах чадвартай, өндөр ургацтай, биохимийн үзүүлэлт сайтай сортыг илрүүлж шалгаруулах зорилготой. Нийт хүнс, тэжээл, шар айрагны 14 сортыг жишиг сорттой ургалтын хугацаа, ургац болон бусад чанарын үзүүлэлтээр харьцуулан судлахад сортуудын боловсрох хугацаа 88-106 хоног, шар айрагны зориулалтаар тарьсан сортууд нь 2.2-14.7 ц/га, тэжээлийн зориулалтынх 6.0-14.8 ц/га, хүнсний зориулалтын арвай нь 2.0-5.5 ц/га ургац өгч байлаа. Шар айрагны сортуудаас МонПиАрвай-5, ПА-459 сортууд жишиг сортоос га талбайгаас 4.3-5.4 ц-ээр, тэжээлийн сортуудаас ТА-453 сорт жишиг сортоос 8.8 ц-ээр илүү ургац өгч шалгарч байна. Харин хүнсний сортуудаас жишиг сортоос ургацаар давсан сорт гарсангүй. Түлхүүр үг: ургалтын хугацаа, ургац, ургацын бүтэц, биохимийн үзүүлэлт